Copyright user rights : contracts and the erosion of property - Chapdelaine, Pascale (OUP, 2017)
"[This book offers] an in-depth investigation of the unsettled nature, scope and dynamics of copyright user rights in an increasingly dematerialized environment. Combining a detailed theoretical framework with practical applications, the book provides a comprehensive perspective on copyright user rights, exploring the nature of commercial copies of copyright works, of exceptions to copyright infringement, and how they are shaped to a large extent by traditional concepts of private law (e.g. property, goods, services, sales, and licences). Using property and contract law and theory, it addresses the competing interests of copyright holders and users in the same object, and points out the double standards in how the rights of copyright holders and copyright users are dealt with. It argues that the property component of user rights has been largely neglected and needs to be brought to the fore, to give the protection that users deserve, without neglecting the rights users should have as they increasingly experience copyright works through services. With the onset of an increasingly digital age, it emphasises how traditional concepts of private law need to adapt for adequately dealing with the dematerialization of copies of copyright works and user rights. It proposes a clearer view on the justification and nature of user rights, with possible gradations of powers for users, and suggests how courts and legislatures may address contract terms that weaken user rights." -- Publisher's website.